Office-based andrology and male infertility procedures—a cost-effective alternative - Alom, Manaf (Transl Androl Urol, 2017)
BACKGROUND: From 2014–2016, our clinical practice progressively incorporated several male infertility and andrology procedures performed under local anesthesia, including circumcision, hydrocelectomy, malleable penile prostheses, orchiectomy, penile plication, spermatocelectomy, testicular prostheses, varicocelectomy, vasectomy reversal (VR), and testicular and microepididymal sperm aspiration (TESE/MESA). Given the observed outcomes and potential financial and logistical benefits of this approach for surgeons and patients, we sought to describe our initial experience. METHODS: A retrospective analysis was performed of all andrologic office-based (local anesthesia only) and select OR (general or monitored anesthesia care) procedures performed from 2014–2016. Financial and outcomes analyses were performed for infertility cases due to the homogeneity of payment modalities and number of cases available. Demographic, clinicopathologic, and procedural costs (direct and indirect) were reviewed and compared. RESULTS: A total of 32 VRs, 24 hydrocelectomies, 24 TESEs, 10 circumcisions, 9 MESA/TESEs, 4 spermatocelectomies, 3 orchiectomies (1 inguinal), 2 microTESEs, 2 testicular prostheses, 1 malleable penile prosthesis, 1 penile plication, and 1 varicocelectomy. Compared to the OR, male infertility procedures performed in the clinic with local anesthesia were performed for a fraction of the cost: MESA/TESE (78% reduction), TESE (89% reduction), and VR (62% reduction). All office-based procedures were completed successfully without significant modifications to technique. Outcomes were similar between the office and OR including operative time (VR: 181 vs. 190 min, P=0.34), rate of vasoepididymostomy (VE) (23% vs. 32%, P=0.56), total sperm counts (72.2 vs. 50.9 million, P=0.56), and successful sperm retrieval (MESA/TESE 100% vs. 100%, P=1.00; TESE 80% vs. 100%, P=0.36). To our knowledge, the current study also represents the first report of office-based VE under local anesthesia alone. For hydrocelectomy procedures, recurrence (4%) and hematoma (4%) rates were low (mean 4.2 months follow-up), although this likely relates to modifications with technique and not the anesthesia or operative setting. Overall, when given the choice, 86% of patients chose an office-based approach over the OR. CONCLUSIONS: Office-based andrology procedures using local anesthesia may be successfully performed without compromising surgical technique or outcomes. This approach significantly reduces costs for patients and the overall healthcare system and has become our treatment modality of choice.